2019
DOI: 10.5812/ijcm.84850
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Breast Cancer (Invasive Lobular and Ductal Carcinoma) Treated with Boost Intraoperative Electron Radiotherapy Versus Conventional External Beam Radiotherapy

Abstract: Background: Breast conserving surgery (BCS) and its following radiotherapy is an accepted therapeutic method for patients with invasive lobular carcinoma (ILC) and invasive ductal carcinoma (IDC). Objectives: The aim of this study was to investigate the effect of intraoperative electron radiotherapy on women with breast cancer (invasive lobular and ductal carcinoma). Methods: Between August 2013 and September 2017, 968 patients, who were referred to Cancer Research Center, Shahid Beheshti University of Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…At the same time, there is substantial evidence supporting the efficacy of IORT 23 , 28 . Likewise, trials have shown that adjuvant radiotherapy controls the loco-regional recurrence 7 , 29 and has an abscopal effect by reducing the risk of distant recurrence 24 , 25 , 30 , 31 . Our previous proteomic and transcriptomic study on the samples of tumor bed before and after IORT illustrated many gene expression modifications that enriched in pathways related to cell growth, survival, program cell death, and cell cycle arrest 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, there is substantial evidence supporting the efficacy of IORT 23 , 28 . Likewise, trials have shown that adjuvant radiotherapy controls the loco-regional recurrence 7 , 29 and has an abscopal effect by reducing the risk of distant recurrence 24 , 25 , 30 , 31 . Our previous proteomic and transcriptomic study on the samples of tumor bed before and after IORT illustrated many gene expression modifications that enriched in pathways related to cell growth, survival, program cell death, and cell cycle arrest 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, which compared the outcome following application of full dose electron beam IORT in 216 early breast cancer patients and 323 external-beam-irradiated cases, revealed that IORT resulted in a lower rate of local recurrence, while external beam radiotherapy resulted in a higher rate of death and systemic recurrence 6 . Furthermore, a 4-year survival study revealed a significantly lower rate of metastases and ipsilateral breast tumor recurrence in Intraoperative Electron Radiotherapy (IOERT)-treated versus conventional radiotherapy-treated patients 7 . Published data suggest that, compared with whole breast radiation therapy, treatment with IORT not only reduces the treatment time 8 but also appears to alter the microenvironment of the irradiated tumor bed.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a study in the cancer research center on 968 patients with breast cancer (IDC and ILC) to compare IOERT (a boost dose) with EBRT. e findings suggested that IOERT was noninferior in comparison with EBRT (P � 0.215) [19].…”
Section: Discussionmentioning
confidence: 95%
“…A study (2013 -2017) was performed on 968 patients with invasive breast carcinoma (ductal and lobular) and compared outcomes of EBRT with IOERT as a boost. It showed that IOERT as boost contained no inferiority in comparison with EBRT (14).…”
Section: Introductionmentioning
confidence: 96%